Pitfalls in the pathological diagnosis of multiple myeloma - V. V. Baykov (Онкогематология)
During 1999-2006, a total of 350 trephine biopsy specimens were evaluated in our department for presence of multiple myeloma. The diagnosis of plasma cell neoplasm was made in 148 cases. In 30% of specimens plasma/myeloma cell count was below 30%, and in 7% - below 10%. Giemsa staining improved detectability of plasma cells. In cases with low plasma cell count immunohistochemistry for CD138 and Ig light chains was able to pick out neoplastic cells and to confirm monoclonality, therefore it was a useful adjunct for morphologic diagnosis. Difficulties in morphological evaluation of trephine biopsies are discussed. It is concluded that the diagnosis of multiple myeloma is based on clinical, laboratory and morphologic data.